Adaptation of a Theory-Based Social Networking and Gamified App-Based Intervention to Improve Pre-Exposure Prophylaxis Adherence Among Young Men Who Have Sex With Men in Bangkok, Thailand: Qualitative Study - Wipaporn Natalie Songtaweesin; Sara LeGrand; Shashika Bandara; Caitlin Piccone; Prissana Wongharn; Juthamanee Moonwong; Thidarat Jupimai; Chutima Saisaengjan; Tuangtip Theerawit; Kathryn Muessig; Lisa Hightow-Weidman; Thanyawee Puthanakit; et al. (JMIR Publications, 2021)
BackgroundHIV disproportionately affects young Thai men who have sex with men (YMSM). Recent studies report a high incidence and prevalence of HIV among Thai YMSM. The Thai national guidelines have recommended pre-exposure prophylaxis (PrEP) since 2014 for key populations; free PrEP has been piloted since 2019. Smartphone-based mobile health (mHealth) interventions provide an optimal platform for innovative PrEP adherence interventions for Thai YMSM. ObjectiveThis study aims to adapt the P3 (Prepared, Protected, emPowered) app, developed with YMSM and transwomen in the United States to improve PrEP adherence and persistence for YMSM in Thailand. The app aims to provide daily adherence support and addresses gaps in staff available for large-scale PrEP rollout needed to see population-level effects of HIV prevention. MethodsWe conducted focus group discussions (FGDs) with YMSM and key informant interviews (KIIs) with PrEP care providers in Bangkok, Thailand, to investigate PrEP adherence facilitators and barriers, preferences for functions and features in mHealth apps among YMSM, and how to best adapt the P3 app to the Thai context. We conducted four FGDs with 4-8 participants per group and 15 KIIs. ResultsFor FGDs, 23 YMSM participated with a mean age of 20 years (range 18-21), 96% (22/23) enrolled in full-time education, and all owned smartphones. The mean age of KII participants was 40 (range 26-60) years; most were state health service providers, with the majority being counselors (6/15, 40%) and physicians (6/15, 40%). Overall, the facilitators and barriers for PrEP adherence identified were similar to those of MSM and YMSM globally including the United States. Key themes included general recommendations for improving mHealth apps in Thailand, such as presenting reliable information in an appealing format, minimizing privacy risks, and addressing connectivity challenges. Additional themes focused on P3 Thailand adaptations and were related to cultural and stylistic preferences, engagement strategies, and recommendations for new functions. To develop the adapted app, P3 Thailand, these findings were balanced with resource limitations resulting in the prioritization of minor modifications: changes in app esthetics (color scheme, iconography, and imagery) and changes in the presentation of information in two of the app's features. FGDs identified similar PrEP adherence facilitators and barriers to those already addressed within the app. ConclusionsThe core elements of the P3 app address major PrEP facilitators and barriers for Thai YMSM; however, changes to the app features, including stylistic presentation, were needed to appropriately customize the app to the Thai context. Given the similarities of facilitators and barriers for PrEP adherence globally, adapting existing PrEP mHealth solutions based on input from end users and key informants provides a promising approach. However, partnerships with local app designers and developers can improve the adaptation process and final product. Trial RegistrationClinicalTrials.gov NCT04413708; http://clinicaltrials.gov/ct2/show/NCT04413708